Use of FRET-Sensor ‘Mermaid’ to Detect Subtle Changes in Membrane Potential of Primary Mouse PASMCs - Dartsch, Ruth C.; Kraut, Simone; Mayer, Tim; Gabel, Andreas; Dietrich, Alexander; Weissmann, Norbert; Fuchs, Beate; Knoepp, Fenja; Justus Liebig University Giessen (My University, 2024)
Subtle changes in the membrane potential of pulmonary arterial smooth muscle cells (PASMCs) are pivotal for controlling pulmonary vascular tone, e.g., for initiating Hypoxic Pulmonary Vasoconstriction, a vital mechanism of the pulmonary circulation. In our study, we evaluated the ability of the fluorescence resonance energy transfer (FRET)-based voltage-sensor Mermaid to detect such subtle changes in membrane potential. Mouse PASMCs were isolated and transduced with Mermaid-encoding lentiviral vectors before the acceptor/donor emission ratio was assessed via live cell FRET-imaging. Mermaid’s sensitivity was tested by applying specific potassium chloride (KCl) concentrations. These KCl concentrations were previously validated by patch clamp recordings to induce depolarization with predefined amplitudes that physiologically occur in PASMCs. Mermaid’s emission ratio dose-dependently increased upon depolarization with KCl. However, Mermaid formed unspecific intracellular aggregates, which limited the usefulness of this voltage sensor. When analyzing the membrane rim only to circumvent these unspecific signals, Mermaid was not suitable to resolve subtle changes in the membrane potential of ≤10 mV. In summary, we found Mermaid to be a suitable alternative for reliably detecting qualitative membrane voltage changes of more than 10 mV in primary mouse PASMCs. However, one should be aware of the limitations associated with this voltage sensor.
Keywords: ddc:610